2D WC single crystal embedded in graphene for enhancing hydrogen evolution reaction. (March 2017) - Zeng, Mengqi; Chen, Yunxu; Li, Jiaxu; Xue, Haifeng; Mendes, Rafael G.; Liu, Jinxin; Zhang, Tao; Rümmeli, Mark H.; Fu, Lei
Abstract: Electrochemical water splitting is regarded as one of the most economical and eco-friendly approaches for hydrogen revolution. Developing a low-cost and earth-abundant non-noble-metal catalyst will be of the most significance. Tungsten carbide (WC) is highly promising due to its platinum (Pt) -like behavior in surface catalysis. Here we first report a liquid metal solvent based co-segregation (LMSCS) strategy to fabricate a high uniformity of 2D WC crystals embedded in graphene by chemical vapor deposition (CVD) in one step. The 2D in-plane WC–graphene heterostructures ( i -WC–G) are remarkably stable under an electro-catalytic environment and ensure good interfacial synergy between the 2D WC crystallites and graphene to achieve a more effective hydrogen evolution. The overpotential is as low as 120 mV and the Tafel slope is 38 mV/dec, which indeed exhibits outstanding catalytic potential among the reported 2D material systems. Our elegant and versatile approach allows the fabrication of other high-quality 2D transition metal carbides (TMCs) and their in-plane heterostructures, which will further promote practical catalytic applications of metal carbides. Graphical abstract: A liquid metal solvent based co-segregation strategy was proposed to fabricate a high uniformity of 2D WC crystals embedded in the few-layer graphene by chemical vapor deposition (CVD) in one step. In addition, the efficient catalytic ability of the 2D WC for the hydrogen evolution, for the first time, was experimentally exhibited. Highlights: A novel liquid metal solvent based co-segregation (LMSCS) strategy was employed to directly fabricate 2D WC single crystals embedded in graphene film, i.e. a unique in-plane heterostructure, over a large scale in one step via chemical vapor deposition (CVD). This 2D in-plane WC–graphene heterostructure ( i -WC–G) was firstly applied in HER. Basing on the high crystallinity of the WC and utilizing the interfacial synergistic catalytic effects, the 2D i -WC–G heterostructure exhibited excellent electrocatalytic activity for the HER. The overpotential was as low as 120 mV and the Tafel slope was 38 mV/decade, which indicated higher performance and efficiency than mainstream 2D HER catalysts. The reproducible polarization plot even after 5000 voltammetry (CV) cycles highlighted the excellent durability of our developed 2D i-WC–G heterostructure. Such a versatile synthesis approach will allow the fabrication of other high-quality 2D transition metal carbides (TMCs) and their embedding in in-plane structures and this will promote the practical catalytic application of metal carbides.